Phytochemical and biological activity study on Pseuduvaria Rugosa (annonaceae) / Hairin Taha - Hairin, Taha (2011)
The study of phytochemical constituents on the bark of Pseuduvaria Rugosa from the family Annonaceae has resulted in the isolation and characterization of aporphine alkaloids, benzo[7]annulene and tripenoids. Six aporphine alkaloids have been isolated from the dichloromethane and methanol crude extract of which three of them are new compounds. The known alkaloids were liriodenine 1, ouregidione 5, and Nmethylouregidione 11, whereas the new alkaloids were 3-amino-1,2-dimethoxy-4,5- dioxoaporphine (pseuduvarine A) 36, N-methyl-3-amino-1,2-dimethoxy-4,5- dioxoaporphine (pseuduvarine B) 37 and 3-hydroxy-1,2-dimethoxy-3,4-dioxoaporphine (pseuduvarine C) 38. The aporphine alkaloids with a substituted amino group at position C-3 in ring A have never been discovered in any plant species before. One compound with the benzo[7]annulene skeleton has been isolated from the methanol extract in very miniscule amount. The structural elucidation of this compound was done based on the mass spectroscopy spectrum and from the fragmentation pattern, this compound was identified as 1-hydroxy-2,3,9-trimethoxy-9-methyl-5H-benzo[7]annulene-5,6,7,8,(9H)- tetraone or Pseuduvarin 39. This compound is a novel compound and has never been isolated before. From the hexane extract, some of the compounds identified by GCMS were terpenoids and most of them were sesquiterpenes and diterpene including fatty acid esters. The major compounds found in the hexane extract were isoelemicin 40, 1,2,3,4-tetramethoxy- 5-(2-propenyl)benzene 41 and 3-hydroxy-1-propenyl-2- methoxyphenol 42. The other compounds are elemicin 24, spathulenol 29 and caryophyllene oxide 30. The sterol compounds found were stigmasterol 43 and gamma sitosterol 44.This thesis also investigated the antioxidant and cytotoxic activities of the crude extracts and isolated compounds from Pseuduvaria Rugosa. The crude extracts and isolated compounds with sufficient quantities were tested for their radical scavenging activity using DPPH method and cytotoxic activity against selected cancer cell lines using the MTS and MTT assay. Preliminary bioactivity screening showed that the hexane, dichloromethane and methanol extracts of Pseuduvaria rugosa displayed weak to moderate activities in the radical scavenging activity but exhibited significant cytotoxic activities against seven cancer cell lines with more than 80% of cell death at 100 μg/ml. Ouregidione, N-methylouregidione and pseuduvarine C showed moderate cytotoxic activity on seven cancer cell lines. Pseuduvarine A and pseuduvarine B showed potent cytotoxicity against human cancer cell lines, MCF7 (IC50 : 0.9 μM, >50.0 μM), HepG2 (IC50: 21.7 μM, 15.7 μM) and HL-60 cells (IC50 : >50 μM, 12.4 μM).